. Pembuatan Visualisasi Event Layout Interaktif Menggunakan Aplikasi SketchUp : Studi Kasus Event ASPEKSINDO Maritime Festival 2023 - ., Ahmad Husnul Rizkyansyah; ., Annisa Wardhani; ., Firman Syah (Bisnis Event, 2024)
This research explains the use of SketchUp application for effective layout design based on a case studyof the ASPEKSINDO Maritime Festival 2023. This research explores the potential for using one layouttechnology, the SketchUp application. This research use a case study as a method. In the process, theresearchers found several obstacles that hampered the layout design process. Based on these findings,the researchers was able to overcome these obstacles so that the layout process could be completed. Itcan be concluded that the SketchUp application can be used effectively in designing 2D and 3D layoutswith fairly high accuracy. Hope this research can contribute to the development of event technology,and increasing efficiency, such as maximizing space in a venue. Keywords: Aplikasi Layouting, SketchUp, Event Layout, Special Event, Festival